Multilinear Littlewood-Paley estimates with applications to partial differential equations - Fabes, Eugene B. (1982)
We obtain a collection of multilinear Littlewood-Paley estimates, which we then apply to two problems in partial differential equations. The first problem is the estimation of the square root of an elliptic operator in divergence form, and the second is the estimation of solutions to the Cauchy problem for nondivergence-form parabolic equations.